2014
DOI: 10.1248/bpb.b14-00055
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Asiatic Acid in Rat Model of Focal Embolic Stroke

Abstract: Asiatic acid (AA) is a pleiotropic neuroprotective agent that has been shown to attenuate infarct volume in mouse and rat models of focal ischemia and has a long clinically relevant therapeutic time-window. Because in a future trial AA would be administered with tissue-plasminogen activator (t-PA), the only approved acute stroke therapy, we sought to determine the effect of AA when co-administered with t-PA in a rat focal embolic stroke model. Male rats were treated with AA (75 mg/kg) alone, low-dose t-PA (2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Numerous active CAW compounds are currently being examined in our laboratory to elucidate their effects on cognitive function, oxidative stress, and mitochondrial biogenesis and function. Previously, in vitro studies have shown that both CAW whole extract and isolated compounds (detailed in a review [32]) facilitate neurite outgrowth [6,28,106], and elicit neuroprotection [107][108][109][110][111]. The neurological effects of certain CAW active compounds are also observed in vivo, increasing learning and memory while providing neuroprotection in rodents [2,13,112].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous active CAW compounds are currently being examined in our laboratory to elucidate their effects on cognitive function, oxidative stress, and mitochondrial biogenesis and function. Previously, in vitro studies have shown that both CAW whole extract and isolated compounds (detailed in a review [32]) facilitate neurite outgrowth [6,28,106], and elicit neuroprotection [107][108][109][110][111]. The neurological effects of certain CAW active compounds are also observed in vivo, increasing learning and memory while providing neuroprotection in rodents [2,13,112].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, asiatic acid has outstanding advantages in reducing inflammation, caring for the skin, and protecting the liver and nerves. It protects the skin from light damage [26,27], prevents liver fibrosis [28,29], protects neurons [30,31],and so forth, and hence it is better at preventing and fighting against skin cancer, liver cancer, glioma, and glioblastoma. Currently, asiatic acid has not been used clinically in the treatment of patients with a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its abundant presence in many plants, AA used as a main biomarker component in numerous plant extract based formulations for standardization and quality assurance (Lee et al, 2014 ). The contents of AA in numerous plant species cultivated, harvested, and habituated from diverse geographic and biodiversity regions have been studied using modern bioanalytical instrumentation techniques.…”
Section: Sources Chemistry and Physicochemical Properties Of Aamentioning
confidence: 99%